Marriage Unregisterred After Decision Constitutional Court and Population Administration Policies: Ulama Perspectives, Implications and Solutions - Nugraha, Alfajar; Qonita, Zahidah Alvi; Awalluddin, Awalluddin (FASYA Press, 2024)
Marriage Unregisterred are a long-standing problem that has never been resolved, especially after the arrival of decision number 46 /PUU-VIII/2010 and the policy of the Population and Civil Registration Service regarding registration of marriages for couples who have not officially married and registered at the Office of Affairs. Religion, this also causes disharmony regarding the opinions of ulama, such as the fatwa of the Indonesian Ulema Council, and Muhammadiyah which opposes the process of unregistered marriages by declaring the marriage annulled, while Nahdatul Ulama, on the other hand, states that the provisions on registration of marriages cannot annul or not validate a marriage because it is not harmonious. and conditions of marriage, from the results of the research analysis it can be illustrated that in the context of a legal state, marriage registration is a benefit and deviation from it is a harm, therefore it is necessary to have registration as a form of protection of the status and rights of someone in the marriage, by Therefore, in this case, it is necessary to strengthen solutions related to prevention and protection for someone who has married unregistered, namely by having a marriage isbat institution and comprehensive outreach regarding the impact of unregistered marriages so as to make people legally aware of the importance of registering their marriages.